A Brontë Reading List: 2020. (3rd April 2023) - Pearson, Sara L.; Cook, Peter; Ogden, James
Abstract: This reading list is an annotated bibliography of selected scholarly and critical work on the Brontës published in 2020. 1 Bibliographical details are followed where possible by summaries and assessments. The list covers most book chapters and peer-reviewed articles on the Brontës, but it is not comprehensive. Articles published in Brontë Studies are as a rule excluded, as are books reviewed in Brontë Studies ; readers are directed to the publisher's website, www.tandfonline.com, for online access to these reviews. The author of each entry is indicated by the author's initials in brackets following the entry.